2000
DOI: 10.1177/0146167200267001
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping Against Your Will: The Role of Inhibitory Ability in Stereotyping and Prejudice among the Elderly

Abstract: An experiment examined the hypothesis that elderly people rely on stereotypes more, and are more prejudiced, than younger people because of deficits in the ability to inhibit information. Consistent with predictions, elderly people relied on stereotypes even when instructed not to, whereas young people did not. Elderly people also were more prejudiced than young people, and these differences in stereotyping and prejudice were mediated by age differences in inhibitory ability. Because elderly people reported a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
146
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 48 publications
16
146
1
2
Order By: Relevance
“…Given that the ability to inhibit automatically activated stereotypes enables people to behave non-prejudicially (Bartholow, Dickter, & Sestir, 2006;Devine, 1989;Moskowitz, Gollwitzer, Wasel, & Schaal, 1999), and inhibitory functioning declines with age (Connelly, Hasher, & Zacks, 1991;Hasher & Zacks, 1988), losses in inhibitory ability may increase stereotyping and prejudice during old age, even if the underlying attitudes are of equivalent (or even declining) strength across the life span (von Hippel, Silver, & Lynch, 2000). This inhibitory deficits account proposes that people of all ages have racially biased associations, but older adults are less able to suppress their associations.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the ability to inhibit automatically activated stereotypes enables people to behave non-prejudicially (Bartholow, Dickter, & Sestir, 2006;Devine, 1989;Moskowitz, Gollwitzer, Wasel, & Schaal, 1999), and inhibitory functioning declines with age (Connelly, Hasher, & Zacks, 1991;Hasher & Zacks, 1988), losses in inhibitory ability may increase stereotyping and prejudice during old age, even if the underlying attitudes are of equivalent (or even declining) strength across the life span (von Hippel, Silver, & Lynch, 2000). This inhibitory deficits account proposes that people of all ages have racially biased associations, but older adults are less able to suppress their associations.…”
Section: Introductionmentioning
confidence: 99%
“…A recognition memory task was used, in which participants read lists of sentences describing men and women carrying out stereotyped and neutral daily activities, and then had to recognize them intermixed with distractor sentences. Data were analyzed by mixed ANOVAs and showed that the sample as a whole exhibited a memory benefit for gender stereotyped over neutral stimuli, and that, as predicted, middle aged adults showed almost twice the memory benefit than young adults and adolescents.Keywords: stereotypes, gender, memory, concepts Existe evidencia de que los adultos tienden a usar estereotipos de género con mayor intensidad que los jóvenes (e.g., von Hippel, Silver & Lynch, 2000). Una explicación simple es que esos adultos habrían crecido en una época menos liberal que la actual y que estuvieron expuestos en un mayor grado a estereotipos.…”
mentioning
confidence: 99%
“…Keywords: stereotypes, gender, memory, concepts Existe evidencia de que los adultos tienden a usar estereotipos de género con mayor intensidad que los jóvenes (e.g., von Hippel, Silver & Lynch, 2000). Una explicación simple es que esos adultos habrían crecido en una época menos liberal que la actual y que estuvieron expuestos en un mayor grado a estereotipos.…”
unclassified
“…En este contexto de creciente relevancia, son numerosas las investigaciones psicosociales y sociológicas basadas en encuesta que muestran una relación de sentido positivo entre edad y prejuicio en población adulta, tanto en Norteamérica como en Europa (véase una revisión en Pettigrew, 2006, Palacios, Torres& Mena, 2009). Asimismo se ha contrastado la estereotipia y el prejuicio en personas mayores con la evolución de estos fenómenos en personas jóvenes (Alvarez, Palmero & Jiménez, 2011;Gonsalkorale, Sherman, & Klauer, 2009;Hippel, Silver & Lynch, 2000;Stewart, Hippel, & Radvansky, 2009), mostrando la menor capacidad en las personas mayores para inhibir las asociaciones estereotipadas y el prejuicio.…”
unclassified